The Big Problem With Little Interruptions to Classroom Learning - Matthew A. Kraft; Manuel Monti-Nussbaum (SAGE Publishing, 2021)
Narrative accounts of classroom instruction suggest that external interruptions, such as intercom announcements and visits from staff, are a regular occurrence in U.S. public schools. We study the frequency, nature, duration, and consequences of external interruptions in the Providence Public School District (PPSD) using original data from a district-wide survey and classroom observations. We estimate that a typical classroom in the PPSD is interrupted more than 2,000 times per year and that these interruptions and the disruptions they cause result in the loss of between 10 and 20 days of instructional time. Several findings suggest that there exists substantial scope for reducing interruptions. Administrators appear to systematically underestimate the frequency and negative consequences of interruptions. Furthermore, interruptions vary widely across schools and are largely caused by school staff. Schools might reduce disruptions to the learning environment by creating a culture that prioritizes instructional time, instituting better communication protocols, and addressing the challenges posed by student tardiness.